Magnetoelastic studies of Nd0.75Dy0.25Fe3(BO3)4 in the external magnetic field: Magnetic phase transitions - Zvyagina, G.A.; Zhekov, K.R.; Bilych, I.V.; Zvyagin, A.A.; Gudim, I.A.; Temerov, V.L.; Eremin, E.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We report on results of sound-velocity and sound-attenuation measurements in the Nd0.75Dy0.25Fe3(BO3)4 in external magnetic fields up to 5 T, applied along several directions with respect to crystallographic axes, and at temperatures down to 1.7 K. The experimental data are analyzed with a microscopic theory based on exchange-striction coupling and phenomenological theory resulting in a qualitative agreement between theoretical results and experimental data.